Integrating Blooket as a Digital Gamification Tool to Enhance Arabic Syntax Learning Outcomes - Dedi Wahyudi; Zulli Umri Siregar; Muhammad Aceng Tata; Erma Febriani (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the effectiveness of Blooket, a gamified learning platform, in enhancing students’ mastery of Arabic syntax (tarkīb) at Darussalam Islamic Junior High School, Wanaraja, Garut. Employing a quantitative approach with a quasi-experimental Non-Equivalent Pre-test and Post-test Control Group Design, the research involved two groups: an experimental class (n = 30) using Blooket and a control class (n = 28) receiving conventional instruction. Data were collected through pre- and post-tests focusing on sentence construction, syntactic recognition, and transformations of jumlah ismiyyah and jumlah fi'liyyah. The data were analyzed using t-tests after confirming normality and homogeneity through Shapiro-Wilk and Levene’s tests. Results indicate a significant improvement in the experimental group’s mean score from 37.67 to 72.40, while the control group’s score increased marginally from 40.00 to 43.39. The independent t-test showed a statistically significant difference in post-test scores (p < 0.05) favoring the experimental group. The experimental group’s normalized gain (N-gain) averaged 0.54 (moderate), compared to 0.02 (low) in the control group. These findings suggest that Blooket can effectively increase student engagement and syntactic understanding in Arabic grammar. However, the low-to-moderate N-gain also highlights the need for prolonged intervention or blended strategies for deeper conceptual mastery. Future research is recommended to investigate the long-term effects of Blooket on various aspects of Arabic language proficiency, including speaking and writing skills. Studies should also examine the integration of Blooket with other pedagogical models to enhance critical thinking, collaboration, and deeper syntactic competence across diverse student populations.